THU0022 Systemic Lupus Erythematosus Increases Risk of Mortality among Patients with Acute Pancreatitis: Findings from A US National Hospital Registry. (10th June 2014) - Mazumder, N.K.; Trivedi, P.; Mujib, M.; Mehta, B.; Mujib, N.; Aronow, W.S.; Efthimiou, P.; Toronjadze, T.; Beekman, K.; Kim, J.H.
Abstract : Background: Acute pancreatitis is a rare presentation among systemic lupus erythematosus (SLE) patients. However, the association of SLE and clinical outcomes among acute pancreatitis has not been studied. Objectives: To study the effect of SLE and in-hospital mortality among patients hospitalized with acute pancreatitis from a US national database. Methods: We used the 2002-2010 Nationwide Inpatient Sample (NIS) databases to evaluate patients who were hospitalized for acute pancreatitis (ICD 9 code 577.0). Discharge weights were used to enable nationwide estimates. Of a total of approximately 80 million hospitalizations in NIS databases, 2.3 million were hospitalized for acute pancreatitis, of which, 14, 553 (0.6%) had SLE. Multivariable logistic regression models were used to assess the effect of SLE on in-hospital mortality among these patients. Results: Acute pancreatitis patients had a mean age of 53 (±18) years and 49% were women. Race distribution comprised of 50% Caucasians, 13% African-Americans and 10% Hispanics. In-hospital mortality occurred in 1.5% and 1.2% of patients with and without SLE respectively (unadjusted odds ratios, 1.26; 95% confidence intervals, 1.10-1.44; P=0.001). After controlling for patient risk factors, hospital characteristics, SLE patients independently conferred the higher adjusted odds of in-hospital mortality (adjusted odds ratios, 1.86; 95% confidence intervals, 1.62-2.14; P<0.001). Acute pancreatitis patients with SLE had a longer mean length of stay (mean stay, 7 vs 5 days, P<0.001) and a higher mean hospital charges ($33, 984 vs. $27, 126 P<0.001). Conclusions: In this nation-wide study, SLE was rare among acute pancreatitis hospitalizations and was independently associated with in-hospital mortality. SLE in acute pancreatitis was also associated with longer length of hospital stay and an increased hospital cost. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5410